First record of the genus Hiroshiinoueana Kawabe, 1978 (Lepidoptera: Tortricidae: Olethreutinae), with a new record and a new species from Thailand - Pinkaew, Nantasak; Muadsub, Sopita (Zootaxa, 2021)
The genus Hiroshiinoueana Kawabe, 1978 is recorded for the first time from Thailand. H. partita sp. nov. is described as new to science. The genus Atsusina Razowski, 2009 is treated as a junior synonym of Hiroshiinoueana. Atsusina curiosissima Razowski, 2009 is transferred to Hiroshiinoueana curiosissima (Razowski, 2009), new record for Thailand and redescribed. Female of H. curiosissima is described for the first time. Illustrations of adults and genitalia are provided. These taxa increase the number of described Hiroshiinoueana to 6 species worldwide.